Consumer Protection in Real Estate Transactions Adjacent to Near River Boundaries - Taniaswari, Vioneta Rizky; Sakti, Muthia (Magister Hukum Universitas Semarang, 2024)
This research aims to determine the effectiveness of consumer protection efforts in purchasing houses near riverbanks, focusing on legal aspects, consumer rights, and dispute resolution. This research is urgent to conduct considering the increasing vulnerability of consumers in property transactions that can potentially increase the risk of violations of consumer rights, economic stability, and public security. The research method used is normative legal research, which allows for an in-depth review of existing laws and regulations governing consumer protection in property transactions, with a thorough analytical approach to the role of regulation and government involvement in responding to developers' failure to comply with rules when constructing buildings, resulting in harm to consumers. The outcome of this research is to propose solutions for regulatory evaluation to enhance consumer protection and ensure fairness and balance in housing transactions, emphasizing the critical role of the legal framework in protecting consumer rights.